Clinical study of hypertensive crisis at a tertiary care hospital of South India - Varun, M. Sai; Gangaram, Usham; Nagabushana, M. V.; Siddappa, H. G. Revana; Soren, Bhimasen (International Journal of Advances in Medicine, 2018)
Background: Hypertensive crisis is a severe clinical condition in which sudden increase in arterial blood pressure can lead to acute vascular damage of vital organs. So timely detection, evaluation and adequate treatment are crucial to prevent permanent damage to vital organs. The aim of the present study is to evaluate incidence and clinical presentation of hypertensive crisis in relation to age, sex, severity of hypertension, accompanying symptoms and clinical manifestations. Methods: It is a clinical prospective study done during the period between January to June 2018 at Narayana Medical College, Nellore. All patients who were more than 18 years with blood pressure>180/120 mmHg to the emergency, outpatients, and inpatients were included. A thorough History and clinical examination was done and necessary investigation was sent to the laboratory. Results: The study results indicate that males (64%) were significantly over represented compared to females (36%). Out of 50 patients majority of the subjects belonged to age group of 50-59 years. Out of 50 Patients most common symptom is Headache (48%), Vomiting (48%), Giddiness (38%), Dyspnoea (22%), Loss of consciousness (22%) followed by chest pain (20%), Blurring of vision (20%) and weakness of limbs (14%). Most of the individuals are in the hypertensive emergency (66%) followed by Hypertensive urgency (34%). Out of 50 patients 56% had neurological involvement and 44% had cardiological involvement. Our study states that most of cases were in grade 1retinopathy (8%) followed in order by grade 4 retinopathy (8%), grade 2 retinopathy (6%) and grade 3 retinopathy (6%). Conclusions: The present study concludes that majority of patients present presenting in hypertensive emergency belonged to fifth and sixth decades of age. So, treating physician should rapidly assess the differentiation of hypertensive emergency and hypertensive urgency in order to prevent end organ damage and to prevent further morbidity and mortality.